La lectura en la neuroplasticidad - Romero Jàcome, Gicelle Aracelly (2025)
The central problem of this research was that during aging, functions such as memory, attention, reasoning, and language deteriorate. This phenomenon has generated an urgent need to develop alternatives that allow this group to access a quality life and preserve their autonomy, independence, and cognitive abilities; in this way, they can remain active and continue acquiring skills and developing new ones. Therefore, the main objective is to explain the importance of reading in neuroplasticity processes in older adults at the Padre Saturnino López Novoa Geriatric Center. Its importance focuses on the fact that reading is a feasible tool that allows older adults to put into practice mental functions such as decoding information, interpretation, making predictions, analyzing and synthesizing information, constructing arguments, and associating experiences with information from history in such a way that this process contributes to the stimulation of cognitive skills such as memory, attention, reasoning and language, which are part of neuroplasticity, a process in which the brain is able to create connections and reorganize its structure. Moreover, functions that allow the elderly to preserve their cognitive functions, decreasing the probability of suffering from mental illnesses or disorders. The research was developed through a qualitative approach; participant observation and interviews were used as instruments for data collection. A field diary, observation guide, and interview guide were used. The six older adults participating in the reading sessions were selected from an intentional non-probabilistic sample. At the end of these sessions, the main findings were that the older adults were able to remember and retain information related to reading and personal experiences more efficiently, maintain attention without being distracted, analyze, reflect and communicate their emotions and ideas more transparently, and coherently, and they also reflected tremendous enthusiasm, joy and self-confidence